Pengaruh Agresivitas Pajak, Komite Audit dan Ukuran Perusahaan terhadap Corporate Social Responsibility Disclosure: Dimoderasi oleh Profitabilitas - Djenni Sasmita; Helny Helny; Anita Ade Rahma (Owner : Riset dan Jurnal Akuntansi, 2025)
The purpose of this study is to determine the Influence of Tax Aggressiveness, Audit Committee, and Company Size on Corporate Social Responsibility Disclosure with Profitability as a Moderator in Property & Real Estate Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 Period. The population of this study includes all Property & Real Estate companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The sampling technique uses the purposive sampling technique. Based on the criteria that have been set, 18 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The results of the study show that Tax Aggressiveness, Audit Committee and Company Size and the interaction variables between each independent variable and the moderation variable, namely Profitability, together have an influence on Corporate Social Responsibility Disclosure. The results of the study show that Tax Aggressiveness has no effect on Corporate Social Responsibility Disclosure, the Audit Committee has a positive effect on Corporate Social Responsibility Disclosure, and Company Size has a negative effect on Corporate Social Responsibility Disclosure. The moderation variable test shows that Profitability can moderate and weaken the influence of Tax Aggressiveness on Corporate Social Responsibility Disclosure, Profitability cannot moderate the influence of the Audit Committee on Corporate Social Responsibility Disclosure and Profitability cannot moderate the influence of Company Size on Corporate Social Responsibility Disclosure.